PENGEMBANGAN MEDIA BONEKA JARI (BOJAR) BERBASIS KEARIFAN LOKAL TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV - NUR KHOLISOH AGUSTIANI; Rina Yuliana; M Taufik M Taufik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Speaking skill refers to the ability of student to convey ideas they have. This research was conducted by using a questionnaire method in R&D research by collecting data through observation and interviews. The purpose of this study was to produce feasible (valid)  finger puppet media based on local wisdom for the students’ speaking skills at grade IV SDN Cikande Permai. This study utilized R&D model proposed by Sugiyono (2010:409) consisting of six steps, namely: (1) Analysis of Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Product Testing. The products were tested on the teacher and students at grade IV by taking a sample of 10 students. The validation result from material experts was 87% while the validation result from the linguists was 84%; and the validation result from media experts was 83%, with the criteria of very feasible, so that the product could be used as the learning media. Moreover, the field trial was conducted by distributing students’ response questionnaire. The results of the questionnaire obtained a percentage of 9.37% with a very good category. Thus, it could be concluded that local wisdom – based finger puppet media was declared feasible to be used in learning.